Physiological Stress Response to Sulfide Exposure of Freshwater Anaerobic Methanotrophic Archaea - Echeveste Medrano, Maider; Lee, Sarah; de Graaf, Rob; Holohan, Conall; Sánchez Andrea, Irene; Jetten, Mike; Welte, Cornelia (American Chemical Society, 2025)
Freshwater wetlands and coastal sediments are becoming hotspots for the emission of the greenhouse gas methane. Eutrophication-induced deposition of organic matter leads to elevated methanogenesis and sulfate reduction, thereby increasing the concentrations of methane and toxic sulfide, respectively. However, the effects of sulfide stress on the anaerobic methanotrophic biofilter have not been well explored. Here, we show how an enrichment culture dominated by the freshwater anaerobic methane-oxidizing archaeon “Candidatus (Ca.) Methanoperedens” responds to short-term and long-term exposure to sulfide in a bioreactor. The methane-oxidizing activity decreased to 45% and 20% but partially recovered to 70% and 30% within 5 days after short- and long-term sulfide exposure, respectively. Metagenomics indicated that “Ca. Methanoperedens” remained dominant in the enrichment throughout the entire experiment. The first short-term sulfide pulse led to increased expression of genes encoding for sulfide detoxification by low abundant community members, whereas long-term exposure resulted in upregulation of “Ca. Methanoperedens” genes encoding sulfite reductases of group III (Dsr-LP). “Ca. Methanoperedens” consumed polyhydroxyalkanoates during long-term sulfide exposure, possibly to aid in stress adaptation. Together, these results provide a valuable baseline for understanding fundamental ecophysiological adaptations to methane cycling in sulfate- and nitrate-rich aquatic ecosystems.
Keywords: 24 Ciencias de la Vida; ODS 13 - Acción por el clima; ODS 14 - Vida submarina; ANME archaea; sulfide stress; sulfur oxidation; methanotrophy; methane